The Impact of Earnings Per Share, Debt to Equity Ratio, and Company Size on Stock Returns in Miscellaneous Industrial Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (2016-2020) - Lestari, Lestari; Mareta, Sigit (Journal of Accounting and Finance Management, 2024)
This study investigates the impact of earnings per share, debt to equity ratio, and company size on stock returns. The research focuses on manufacturing companies within the miscellaneous industrial sector listed on the Indonesia Stock Exchange during the 2016-2020 period. A purposive sampling technique was employed to select the sample. Descriptive statistics were used as the analytical method, with data analysis conducted using the SPSS application. The findings reveal that earnings per share have a significant negative impact on stock returns, the debt to equity ratio has a significant effect, while company size does not significantly influence stock returns. These results suggest that investors should carefully consider a company's earnings per share and debt to equity ratio when making investment decisions, as these factors significantly affect stock returns. Meanwhile, company size may not be a critical determinant for stock return predictions within this sector.